Resolution of Multiple Severe Nonsteroidal Anti-Inflammatory Drug-Induced Colonic Strictures with Prednisone Therapy: A Case Report and Review of the Literature - Robert M Penner; C Noel Williams (Canadian Journal of Gastroenterology)
A 69-year-old woman on nonsteroidal anti-inflammatory drugs (NSAIDs) was admitted to a university hospital with abdominal pain, profound anemia and melena stools. Duodenal ulceration and subsequent healing were documented. Colonoscopy revealed haustral ulceration and NSAID-induced colonic diaphragm disease. Discontinuation of NSAID therapy did not result in endoscopic change, but a 20-week course of prednisone was followed by complete resolution. This is the first case describing prednisone monotherapy for such strictures, and only the second in which endoscopic resolution has been documented. With further supporting experience, prednisone may be considered in addition to NSAID discontinuation for patients with this rare but serious complication.